Aprendizagem em Vygotsky e em freire: aproximações e especificidades - Trentin, Patrícia Fortunato Fileraz (2012)
This research investigated the meaning of learning in Paulo Freire s and Lev Vygotsky s works in order to determine similarities and specificities in the way the term was used by these two educators. Although the aforementioned authors applied the term in various contexts and in their social practices, this research focused on the analysis of the term as applied in specific works considered central to the purpose of this dissertation. Paulo Freire s examined books were: Pedagogy of the Oppressed, The Importance of the Act of Reading, Pedagogy of the Heart, Pedagogy of Hope and Pedagogy of Freedom. Vygotsky s analyzed texts were: Mind in Society: The Development of Higher Psychological Processes, Language development and learning, Thought and Language, and Educational Psychology. This study concluded that despite the contextual differences of their experiences and field of studies, the authors main theses seem to converge. However, in the work of Freire, it is possible to verify greater emphasis on the collective and political dimension of knowledge, whereas Vygotsky s works tend to focus on the cognitive processes of learning.